Discordant Expression of Circulating microRNA from Cellular and Extracellular Sources - Shah, Ravi; Tanriverdi, Kahraman; Levy, Daniel; Larson, Martin; Gerstein, Mark; Mick, Eric; Rozowsky, Joel; Kitchen, Robert; Murthy, Venkatesh; Mikalev, Ekaterina; Freedman, Jane E. (PLOS ONE, 2016)
MicroRNA (miRNA) expression has rapidly grown into one of the largest fields for disease characterization and development of clinical biomarkers. Consensus is lacking in regards to the optimal sample source or if different circulating sources are concordant. Here, using miRNA measurements from contemporaneously obtained whole blood- and plasma-derived RNA from 2391 individuals, we demonstrate that plasma and blood miRNA levels are divergent and may reflect different biological processes and disease associations.